Study of the contrasting effectiveness of various tumors types using cubic magnetite nanoparticles - A. A. Nikitin; V. A. Naumenko; S. S. Vodopyanov; A. S. Garanina; N. D. Fedorova; E. D. Kalabay; A. G. Savchenko; M. A. Abakumov; A. G. Majouga (Бюллетень сибирской медицины, 2018)
Currently magnetic resonance imaging (MRI) is one of the key diagnostics methods of various diseases. Utilizing various contrast agents based on magnetic nanoparticles can improve the diagnostic efficiency and, consequently, the quality of the subsequent treatment. The most promising contrast agents are cubic magnetite nanoparticles, due to their high relaxation rates, as well as biocompatibility and biodegradability.Thereby, the purpose of this work was to evaluate the effectiveness of MRI imaging of tumors by cubic magnetite nanoparticles (CMN).Materials and methods. For this purpose, the synthesis of 15 nm CMN modified with biocompatible copolymer plurlonic F127 was carried out. Synthesized CMN and their water colloids were characterized by a complex of physicochemical methods of analysis. Then, using MRI a study of the effectiveness of contrasting of various tumor types after intravenous administration of CMN aqueous colloids was made. Three models of mouse tumors were used for a comprehensive assessment of obtained results: breast cancer 4T1, colon cancer CT-26 and melanoma B16. MRI studies were performed prior to the administration of the particles, and also after 15 min, 6 hours and 24 hours after injection in T2-weighted regime in two mutually orthogonal projections.Results. The analysis of the obtained results showed that the most effective accumulation of particles was found in the 4T1 (100%) and B16 (57%) models, and in the case of CT-26 model the accumulation efficiency was 50% due to the effect of the permeability of blood vessels.